Analisis Pengaruh Penerapan Ujian Online bagi Siswa menggunakan Technology Acceptance Model (TAM) (Studi Pada SMK Nasional Malang) - Fakhrizal Arif Pratidina; Retno Indah Rokhmawati; Faizatul Amalia (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Current technological advances in exams have used CBT (Computer Based Test) in implementation. National Malang Vocational School is one of the schools that have utilized CBT (Computer Based Test) during the Semester Exams, Final Semester Exams and National Exams. This study used the Technology Acceptance Model to determine the acceptance of an information technology. This model aims to measure how Malang National Vocational School students receive CBT as a method of conducting exams which sometimes still have some problems. To be able to measure it used 7 variables, namely Subjective Norm, Self-efficacy, Perceive Ease of Use, Perceived Usefulness, Technology Innovativeness, Behavioral Intention, Actual Behavior. The data were collected from students of the X and XI Malang National Vocational High Schools with information technology majors and obtained 52 respondents through questionnaires given after the Semester Final Examination was completed. The results of this study indicate that there are other individual influences, self-confidence can influence students' attitudes towards ease of use and benefit of the system. There is no influence between perceptual variables Perceive Ease Of Use towards the variable perception of the usefulness of Perceived Usefulness. Technology innovativeness strengthens the positive influence between Perceive Ease Of Use variables on the variable desire to perform Behavioral intention..